Results of Combined Multispecialty Endoscopic Dacryocystorhinostomy. (August 2013) - Kim, Charles; Kacker, Ashutosh; Pearlman, Aaron N.; Lelli, Gary J.
Abstract Objective: To characterize the pre- and post-operative findings in patients undergoing endoscopic dacryocystorhinostomy (eDCR) performed jointly by ophthalmologists and otolaryngologists. Methods: Retrospective case series consisting of all the patients who underwent eDCR for nasolacrimal duct obstruction at New York Presbyterian Hospital/Weill Cornell Medical College between the 2009–2012 academic years. Patients were followed post-operatively for at least six months. The primary endpoint assessed in this study was symptom recurrence (epiphora). Results: A total of 20 patients (25 total cases) underwent eDCR within the study interval. Of the 25 cases, 7 (28.0%) represented reoperations due to recurrent symptoms. All 20 patients in the study exhibited sinus pathology, as determined during a pre-operative otolaryngology assessment. As a result, 16 of these patients (80.0%) underwent concurrent sinonasal surgery at the time of eDCR. The success rate in cases without prior DCR was 83.3% (15/18). Only 57.1% of revision cases (4/7) reported resolution of epiphora following surgery. Conclusion: While a joint approach to eDCR did not appear to significantly improve efficacy, it offered the advantage of having an otolaryngologist assess and treat concurrent sinonasal pathology, which was seen in every patient in our series. Given our findings, as well as the technical difficulty often associated with the procedure, there may be great utility in performing eDCR in conjunction with an otolaryngologist.